(untitled) (Jurnal Teknologi (Sciences & Engineering), 2024)
Invasive meningococcal disease (IMD) is an acute, severe, and potentially fatal infection caused by Neisseria meningitidis and is a global public health burden. Given the high fatality rate linked to acute bacterial meningitis, it is imperative to initiate treatment and diagnosis concurrently in most cases. While a culture demonstrating the growth of N. meningitidis from blood or cerebrospinal fluid (CSF) remains the gold standard, however, its sensitivity diminishes following antibiotic administration. Therefore, in this study, differentially extracted whole cell protein (WCP), surface depleted whole cell protein (sdWCP), and cell surface protein (CSP) profiles were analysed by using SDS-PAGE to characterise and classify pathogenic N. meningitidis and non-pathogenic species. This study provides clear evidence that SDS-PAGE yields distinct protein patterns across Men A, B, C, and Y, clinical isolates 1 and 2, N. sicca, N. cinerea, and M. catarrhalis. It effectively demonstrates that SDS-PAGE protein profiling can serve as a reliable method for characterising and separating bacterial proteins at both the species and strain levels. Despite the availability of more advanced technologies, SDS-PAGE remains a valuable tool, particularly in settings where advanced equipment and knowledgeable personnel are lacking. Our approach employs various extraction techniques, has successfully defined and characterised N. meningitidis, non-pathogenic Neisseria species, and M. catarrhalis.